Application of the "Principle of the First Reviser" to determine the correct spelling for a recently described stingray species from the Western South Atlantic Ocean (Chondrichthyes, Myliobatiformes, Dasyatidae) ... - Secioso Santos, Hugo Ricardo; Carvalho, Marcelo R. de ([Cysneiros & Cia, 2007)
(Uploaded by Plazi from the Biodiversity Heritage Library) No abstract provided. ...